On wings of eagles - Follett, Ken (William Morrow and Company New York, 1983)
The true story of a former Green Beret commander who led a group of businessmen on a daring rescue mission to free two men from an Iranian jail.
Maps on lining papers.
Keywords: Iranian Hostage Crisis -- 1979-1981; Escapes -- Iran; Diplomatic relations; Iran -- Foreign relations